Recommendation System for Selection of Beach Tourist Attraction in Serdang Bedagai Applying the TOPSIS Algorithm - Annisa Fadillah Siregar (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
One of the regencies in North Sumatra, specifically the Serdang Bedagai Regency, has many exciting beach attractions for the public to visit. Each beach attraction offers its own excellence. In this circumstance, it could be a hesitation which to decide on, considering that there are a great number of beaches lying in the Serdang Bedagai Regency. This research uses five criteria such as facilities, security, hygiene, road access, and price. As well as the alternatives of several beach attractions such as Pondok Indah beach, Mutiara beach, Klang beach, Cermin beach, Romantic beach, Gudang Garam beach, Sri Mersing beach, Bali Lestari beach, Wong Rame beach, and Cemara Kembar beach. Therefore, a system is built to be used for the public in deciding on beach attractions by applying a recommendation system for selecting any beach attractions. According to the calculations in table 3.3 with the RPI as the reference value. The highest RPI value among beach attractions is the Bali Lestari beach with an RPI value of 1, the second is Romantic beach with an RPI value of 0.462, and Cermin beach with an RPI value of 0.462